Odpowiedzi

Najlepsza Odpowiedź!
2009-11-12T12:19:31+01:00
wielomian W(x)=x⁴+5x³-12x²+5x+1 dzieli się przez dwumian (x-1) jeśli W(1)=0 to dzieli się bez reszty
W(1)=1⁴+5*1³-12*1²+5*1+1=1+5-12+5+1=0 czyli dzieli sie bez reszty
W(x)=x⁴+5x³-12x²+5x+1

x³+6x²-6x-1
------------------------------
(x⁴+5x³-12x²+5x+1) : (x-1)
-x⁴+x³
----------------------
6x³-12x²+5x+1
-6x³+6x²
----------------------
-6x²+5x+1
6x²-6x
--------------------
-x+1
x-1
-----------------
= =

W(x)=x⁴+5x³-12x²+5x+1=
=(x-1)(x³+6x²-6x-1)=
=(x-1)(x³-1+6x²-6x)=
=(x-1)[(x-1)(x²+x+1)+6x(x-1)]=
=(x-1)²[(x²+x+1)+6x]=
=(x-1)²[x²+7x+1]
x²+7x+1=0
Δ=49-4=45
√Δ=√45=3√5
x₁=(-7-3√5):2
x₂=(-7+3√5):2
rosnąco :
x₁=(-7-3√5):2, x₂=(-7+3√5):2, x=1